Drying Technologies: Vehicle to High-Quality Herbs - Orphanides, Antia; Goulas, Vlasios; Gekas, Vassilis (My University, 2016)
Herbs are usually marketed as dry due to a consumer demand beyond their seasonality; dehydration leads to a stable, easily moveable product that is available throughout the year. The process of drying, though, leads to modifications in the appearance, composition and quality of the raw material. The extent of these alterations depends on the applied drying methodology and its parameters, rendering the optimization of this process imperative. Numerous studies examining the effect of drying on the main characteristics of herbs have been published in recent years, and this review aims at organizing the available information of the studied herbs, drying methods and measured parameters in a comprehensive manner. Primarily, since aroma is the main characteristic of herbs and the principal aim for the end product is to retain the raw material’s character, this review will focus on the most widely studied effect of drying, which is the essential oil yield and composition. Secondly, results from various studies on the influence of drying on biochemical compounds, organoleptic properties of dried herbs are also presented. The most common approach to the study of drying kinetics is also presented. Finally, novel technologies targeting to minimize the magnitude of changes from the raw material are described.
Keywords: Antioxidants; Microwave drying; Aromatic plants; Convection drying; Essential oil; Freeze drying